COST OF ILLNESS PADA PASIEN PENYAKIT KANKER PAYUDARA DI RSUD ULIN BANJARMASIN - Noor Aisyah; Shela Puji Dina (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2020)
The cost of illness is an important element in disease decision making because it can evaluate the economic burden of disease. One of them is breast cancer because breast cancer is a catastrophic disease. This study aims to determine direct medical costs, direct non-medical costs, indirect costs, and total costs based on a societal perspective in breast cancer patients at Ulin Hospital, Banjarmasin. This study is an observational analytic study with a prevalence-based cost of illness approach. Data was taken retrospectively for direct medical costs collected from patient medical records that met the inclusion and exclusion criteria, patient treatment data, and details of direct medical costs for the period January-July 2020. Direct non-medical costs and indirect costs were taken from the results of filling out a questionnaire to Breast cancer patients who have undergone treatment in the inpatient room of RSUD Ulin Banjarmasin. Data analysis used descriptive statistics to identify patient characteristics and the costs of breast cancer. The results of the study, the average direct medical cost of breast cancer patients at Ulin Banjarmasin Hospital was Rp. 6,281,700. The average direct non-medical cost was Rp. 416,780 and the average indirect cost was Rp. 229,820. Meanwhile, the average overall cost per episode of inpatient was Rp. 6,928,300